Analytical solutions of electromagnetic fields in prismatic regions - Saurabh Kumar, Mukerji; M. B., Ramamurthy; Sandeep Kumar, Goel (MANCHESTER UNIV PRESS, 2008)
To estimate the electromagnetic fields anywhere along a rectangular or circular waveguide, analytical solutions for Maxwell's equations are already available. In this paper analytical solutions for Maxwell's equations are presented for fields along three-dimensional prismatic regions with travelling or standing waves. The solution of the Laplace equation, for prismatic regions with scalar potential field, is also given.